Measurement‐based geometrical characterisation of the vehicle‐to‐vulnerable‐road‐user communication channel. Issue 14 (9th April 2020) - Rashdan, Ibrahim; de Ponte Müller, Fabian; Sand, Stephan; Jost, Thomas; Caire, Giuseppe
Abstract : Vehicle‐to‐vulnerable‐road‐user (V2VRU) communications have the ability to provide 360 ° of awareness to both vehicles and vulnerable road users to prevent accidents. An accurate V2VRU channel model in critical accident scenarios is essential to develop a reliable communications system. Therefore, extensive wideband single‐input and single‐output channel measurement campaigns at 5.2 GHz were carried out in open‐field and urban environments. Accident prone scenarios between a vehicle and a cyclist as well as between a vehicle and a pedestrian are considered. In this study, locations of the scatterers in the propagation environment are estimated. The authors propose a method to extract specular multipath components (MPCs) from the estimated time‐variant channel impulse response based on the density of neighbouring MPCs. The specular MPCs are then tracked using a novel tracking algorithm based on the multipath component distance approach. Each path is then related to a physical scatterer in the propagation environment by employing a joint delay‐Doppler estimation. According to the results, single and double bounce reflections from buildings and parked vehicles are identified in line‐of‐sight (LoS) situation. In non‐LoS(NLoS) situation, scattering from nearby trees as well as reflections from traffic signs and lampposts beneath the trees canopy are identified.